2023
DOI: 10.1080/19490976.2023.2256695
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the inhibitory potential of the antiarrhythmic drug amiodarone against Clostridioides difficile toxins TcdA and TcdB

Judith Schumacher,
Astrid Nienhaus,
Sebastian Heber
et al.

Abstract: The intestinal pathogen Clostridioides difficile is the leading cause of antibiotic-associated diarrhea and pseudomembranous colitis in humans. The symptoms of C. difficile -associated diseases (CDADs) are directly associated with the pathogen’s toxins TcdA and TcdB, which enter host cells and inactivate Rho and/or Ras GTPases by glucosylation. Membrane cholesterol is crucial during the intoxication process of TcdA and TcdB, and likely involved during pore formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Recently, amiodarone, an antiarrhythmic drug blocking potassium, sodium, and calcium channels, was shown to be a potent inhibitor of TcdA and TcdB exotoxins. 165 In an elegant study, the authors demonstrated that amiodarone prevents glucosyltransferase domain release into the cytosol by insertion into and blockage of the toxins’ translocation pore. In vitro , the drug was active against the toxin variants from the clinically relevant epidemic C. difficile strain NAP1/027 at concentrations comparable to those reached in the plasma of patients treated for arrhythmia.…”
Section: Non-antibiotic Small Molecule Agents Against C Difficilementioning
confidence: 99%
“…Recently, amiodarone, an antiarrhythmic drug blocking potassium, sodium, and calcium channels, was shown to be a potent inhibitor of TcdA and TcdB exotoxins. 165 In an elegant study, the authors demonstrated that amiodarone prevents glucosyltransferase domain release into the cytosol by insertion into and blockage of the toxins’ translocation pore. In vitro , the drug was active against the toxin variants from the clinically relevant epidemic C. difficile strain NAP1/027 at concentrations comparable to those reached in the plasma of patients treated for arrhythmia.…”
Section: Non-antibiotic Small Molecule Agents Against C Difficilementioning
confidence: 99%
“…Therefore, the hypocholesterolemic drug simvastatin, which acts as an inhibitor of the HMG-CoA reductase, was found to be capable of inhibiting cell entry of TcdA/B by decreasing the cholesterol content in membranes of cultured cells (Papatheodorou et al 2019 ). Recently, it was shown that the antiarrhythmic drug amiodarone prevents intoxication of cells by TcdA/B (Schumacher et al 2023 ). Amiodarone’s main mode of inhibition likely involves interference with pore formation and translocation of both toxins.…”
Section: Role Of Bacterial Toxins In Traumatic Diseases Barrier Failu...mentioning
confidence: 99%